AUTHENTICITY CRITERIA IN CASTLES OF IVANO-FRANKIVSK REGION - Tikhonova, Olha; Alho, Carlos (European Scientific Journal, ESJ, 2015)
1- The information about castles can change during the time passing. It is important to verify what is authentic in the castles that are under research. 2-The author, based on the case studies about castles and after analyzing the best practices in Europe explores the verification of authenticity and define the fundamental criteria in conservation. Base of the found materials about castles in Ivano- Frankivsk region and taking into consideration the different interdisciplinary views on Conservation create a systematization of detected objects in Ivano – Frankivsk region by the time of their occurrence and the architectural and typological characteristics. It can help to define the authenticity criteria for Conservation of Castles in this area. 3- This criteria can help to define the method of preservation for each castle that was under this investigation. And set the authenticity criteria for Conservation of Castles in this region.